Compost Life Cycle and Unveiling the Journey of Recycling Organic Waste through the Composting Process: Libya as a case study - Beshir Ali Safor (African Journal of Advanced Pure and Applied Sciences, 2024)
The Compost Life Cycle Infographic illustrates the fascinating journey of recycling organic waste through the composting process. It provides a concise visual representation of the different stages of converting organic waste into nutrient-rich compost and highlights the importance of composting for sustainable waste management. The conducted study is considering in Umm Al-Aranib region that located in southern southwest of Libya. The infographic starts by showing the collection of organic waste such as food scraps, garden waste and agricultural residues. These materials are diverted from landfills to composting facilities, reducing the amount of waste that can cause environmental degradation.